Prevalence of dengue fever in Western Uttar Pradesh, India: A gender-based study - Kumar, Manoj; Verma, Rajesh; Mishra, Bishal (International journal of applied and basic medical research, 2020)
Objective: Gender-based serologic differences for nonstructural protein 1(NS1) antigen (Ag) and IgM antibody (Ab) detection have been reported among cases of dengue in few studies. However, to understand its distribution with patient's gender and their demographic profile, this study is designed to fill the gaps in the available gender based data, and is the first from this region. Materials and Methods: A total of 4252 blood samples were collected aseptically during the outbreaks of 2016-17. Serum was separated and processed for dengue ELISA (NS1Ag and IgM Ab). All the relevant clinical data and variables such as gender and their demographic profile were recorded and statistically analyzed. Results: A total of 978 (23%) patients were found seropositive either by NS1 Ag or IgM Ab ELISA. The proportion of male was higher than female among all seropositive cases, with the ratio of (M:F) 1.54:1 (P < 0.0001). The males were predominately more affected compared to females among rural (P = 0.001) and semi-urban (P = 0.016) areas. The positive NS1 (P = 0.004) and IgM (P = 0.0001) both results were significantly associated with male gender. Conclusion: Every case of dengue must be screened for NS1Ag and IgMAb to increase the diagnostic precision, despite the males being more affected as compared to females due to sociocultural differences.